The Comic Development of Fairytale: The Adventures of Two Siblings as A Teaching Material for the Deutsche Literatur Course - Nurlaili Khoirun Nikmah; Sawitri Retnantiti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The research and development aim to produce teaching material in the form of a comic entitled “Märchen: Die Abenteuer von zwei Geschwister“ to help students understand German literature. The development used in this research was the ADDIE model. Product has been validated by a media expert and a material expert and tested on 67 students taking the Deutsche Literature course. The research and development data were obtained from the questionnaires and observations as a research instrument and analyzed using the descriptive qualitative technique. This research showed that comic teaching material could motivated students to learning German literature and helped students to understand German literature, especially fairytales.